Modulator based on K15-10 capacitors for a power supply of the KIU-12 klystron - Akimov, V.E.; Bak, P.A.; Galimov, R.N.; Kazarezov, I.V.; Korepanov, A.A.; Kot, N.H. (Вопросы атомной науки и техники, 1999)
The modulator based on PFN described above has been operated during several hundreds hours at a PFN charge voltage U=20 kV and repetition rate of 50 Hz. At present the klystron and modulator are used for RF power supply of a photogun cavity of VEPP-5 injection complex. PFN testing at operating conditions under a voltage of 40 kV will be carried out in the future.